Gradient lithium-rich manganese-based material, preparation method thereof and application of gradient lithium-rich manganese-based material as battery positive electrode material

By forming a transition layer and a perovskite layer on the surface of the lithium-rich manganese-based positive electrode material, the problems of low Coulomb efficiency, severe voltage attenuation, and low cycling and rate performance are solved, and the high discharge capacity, average discharge voltage and rate performance are improved.

CN119905566AActive Publication Date: 2025-04-29SHANDONG CHUANGNENG NEW MATERIALS CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510130857.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-29
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

In practical applications, lithium-rich manganese-based cathode materials have problems such as low Coulomb efficiency, severe voltage attenuation, and low cycle and rate performance, which limits their application in lithium-ion batteries.

Method used

By modifying the surface of the lithium-rich manganese-based material on the phase structure gradient, the transition layer and perovskite layer are formed, the ionic conductivity and structural stability of the material are improved, thereby inhibiting side reactions and electrochemical degradation.

Benefits of technology

High discharge capacity, average discharge voltage and rate performance are achieved, and the overall electrochemical performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905566A_ABST
    Figure CN119905566A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a gradient lithium-rich manganese-based material, a preparation method thereof and application of the gradient lithium-rich manganese-based material as a battery positive electrode material. According to the gradient lithium-rich manganese-based material provided by the invention, the transition layer and the perovskite layer are modified on the surface of the phase structure gradient lithium-rich manganese-based material, and the perovskite layer is used as an excellent ionic conductor material, can improve the ionic conductivity of the gradient lithium-rich manganese-based material, and also is used as an oxygen buffer solution to reversibly absorb oxygen ions, so that the release of oxygen is hindered, and the performance of the material is improved. The electrochemical window of the cathode material is widened, side reaction, impedance growth and electrochemical degradation on the surface of the gradient lithium-rich manganese-based material are inhibited, and the discharge capacity, average discharge voltage and rate capability of the battery are improved. The gradient lithium-rich manganese-based material provided by the invention is high in discharge capacity, high in average discharge voltage, high in rate capability and excellent in electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and particularly relates to a gradient lithium-rich manganese-based material, a preparation method thereof, and an application as a cathode material of a battery. Background Art

[0002] With the rapid development of pure electric vehicles and plug-in hybrid electric vehicles, the improvement of the energy density and cycle performance of lithium-ion batteries has become the focus of attention in the current energy field.

[0003] Lithium-rich manganese-based cathode materials are considered to be the most promising cathode materials for next-generation power batteries due to their advantages of high specific capacity (>250 mAh / g), high working voltage, and high safety. However, problems such as low initial Coulomb efficiency, severe voltage decay, and low cycle and rate performance of lithium-rich manganese-based cathode materials limit their practical applications. Researchers have improved their electrochemical performance to a certain extent by modifying lithium-rich manganese-based cathode materials. However, the overall discharge performance is still insufficient. Summary of the Invention

[0004] The purpose of the present invention is to provide a gradient lithium-rich manganese-based material, a preparation method thereof, and an application as a cathode material of a battery. The gradient lithium-rich manganese-based material provided by the present invention has a high discharge capacity and a high average discharge voltage.

[0005] In order to achieve the above purpose, the present invention provides the following technical solutions:

[0006] The present invention provides a gradient lithium-rich manganese-based material, including a phase structure gradient lithium-rich manganese-based material, a transition layer covering the surface of the phase structure gradient lithium-rich manganese-based material, and a perovskite layer covering the surface of the transition layer; the chemical formula of the phase structure gradient lithium-rich manganese-based material is xLi 2 MnO 3 ·(1 - x)LiTMO 2 - yLi 2 MnO 3 ·(1 - y)LiTMO 2 , 0 < y < x < 1, the TM element is Ni, Co, and Mn; the chemical formula of the perovskite layer is A 1-w B w TMO 3 , 0 ≤ w < 1, the A element is one or more of La, Sm, Ba, Sr, and Pr, the B element is one or more of Fe, Mo, and Cr, and the TM element is Ni, Co, and Mn; the transition layer is a phase structure gradient lithium-rich manganese-based material doped with A elements and B elements, and the contents of the A elements and B elements independently increase from the inside to the outside.

[0007] Preferably, the particle size of the phase structure gradient lithium-rich manganese-based material is 1 - 30 μm.

[0008] Preferably, the thickness of the transition layer is 2-10 nm.

[0009] Preferably, the thickness of the perovskite layer is 2 to 10 nm.

[0010] Preferably, in the perovskite layer, the molar ratio of Ni to Co is 0.05-0.3:0.05-0.2; the molar ratio of Ni to Mn is 0.05-0.3:0.5-0.9.

[0011] Preferably, the chemical formula of the phase structure gradient lithium-rich manganese-based material is: core center 0.5Li 2 MnO 3 0.5Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2 , 0.3Li on the nuclear surface 2 MnO 3 0.7Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2 .

[0012] Preferably, the chemical composition of the perovskite layer is La 0.5 Fe 0.5 Ni 0.294 Co 0.112 Mn 0.594 O 3 、Sm 0.5 Mo 0.5 Ni 0.294 Co 0.112 Mn 0.594 O 3 ,La 0.3 Fe 0.7 Ni 0.294 Co 0.112 Mn 0.594 O 3 、PrNi 0.294 Co 0.112 Mn 0.594 O 3 、SmNi 0.294 Co 0.112 Mn 0.594 O 3 、BaNi 0.294 Co 0.112 Mn 0.594 O 3 or SrNi 0.294 Co 0.112 Mn 0.594 O3 .

[0013] The present invention also provides a method for preparing the gradient lithium-rich manganese-based material described in the above scheme, characterized in that it comprises the following steps:

[0014] The A source, the B source, water and the phase structure gradient lithium-rich manganese-based material are mixed and adsorbed and then annealed to obtain the gradient lithium-rich manganese-based material.

[0015] Preferably, the annealing temperature is 500-900° C., and the annealing time is 4-10 hours; the annealing atmosphere is one or more of air and oxygen.

[0016] The present invention also provides the use of the gradient lithium-rich manganese-based material described in the above scheme or the gradient lithium-rich manganese-based material obtained by the preparation method described in the above scheme as a positive electrode material for a battery.

[0017] The present invention provides a gradient lithium-rich manganese-based material. The gradient lithium-rich manganese-based material provided by the present invention is modified with a transition layer and a perovskite layer on the surface of the phase structure gradient lithium-rich manganese-based material. The perovskite layer, as an excellent ion conductor material, can improve the ion conductivity of the gradient lithium-rich manganese-based material, and at the same time, as an oxygen buffer, it reversibly absorbs oxygen ions, thereby hindering the release of oxygen, broadening the electrochemical window of the cathode material, inhibiting side reactions, impedance growth and electrochemical degradation on the surface of the gradient lithium-rich manganese-based material, and improving the discharge capacity, average discharge voltage and rate performance of the battery. The gradient lithium-rich manganese-based material provided by the present invention has high discharge capacity, high average discharge voltage, high rate performance, and excellent electrochemical performance. The results of the examples show that the gradient lithium-rich manganese-based material provided by the present invention has a discharge specific capacity of 265mAhg at 0.2C. -1 Above, the discharge capacity of 5C is 165mAhg -1 Above, the average discharge voltage is above 3.65V.

[0018] The present invention also provides a method for preparing the gradient lithium-rich manganese-based material of the above scheme. The present invention obtains a transition layer with varying doping elements and an ultra-thin perovskite layer by surface modification of the phase structure gradient lithium-rich manganese-based material. The preparation method provided by the present invention has simple steps and is suitable for large-scale production.

[0019] The present invention also provides the application of the gradient lithium-rich manganese-based material described in the above scheme or the gradient lithium-rich manganese-based material obtained by the preparation method described in the above scheme as a positive electrode material for a battery. The gradient lithium-rich manganese-based material provided by the present invention has high discharge capacity, high average discharge voltage, and high rate performance, and can meet the requirements of batteries, especially lithium-ion batteries, for positive electrode materials, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the accompanying drawings required in the embodiments. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other accompanying drawings can be obtained based on these drawings.

[0021] Figure 1 It is a schematic structural diagram of the gradient lithium-rich manganese-based material prepared in Embodiment 1 of the present invention;

[0022] Reference numerals: 1 is the phase structure gradient lithium-rich manganese-based material, 2 is the transition layer, and 3 is the perovskite layer. Detailed implementation manners

[0023] The present invention provides a gradient lithium-rich manganese-based material, including a phase structure gradient lithium-rich manganese-based material, a transition layer covering the surface of the phase structure gradient lithium-rich manganese-based material, and a perovskite layer covering the surface of the transition layer; the chemical formula of the phase structure gradient lithium-rich manganese-based material is xLi 2 MnO 3 ·(1 - x)LiTMO 2 -yLi 2 MnO 3 ·(1 - y)LiTMO 2 , 0 < y < x < 1, and the TM element is Ni, Co, and Mn; the chemical formula of the perovskite layer is A 1-w B w TMO 3 , 0 ≤ w < 1, the A element is one or more of La, Sm, Ba, Sr, and Pr, the B element is one or more of Fe, Mo, and Cr, and the TM element is Ni, Co, and Mn; the transition layer is a phase structure gradient lithium-rich manganese-based material doped with A elements and B elements, and the contents of the A element and the B element independently increase from the inside to the outside.

[0024] The gradient lithium-rich manganese-based material provided by the present invention includes a phase structure gradient lithium-rich manganese-based material (inner core); the chemical formula of the phase structure gradient lithium-rich manganese-based material is xLi 2 MnO 3 ·(1 - x)LiTMO 2 (core center) - yLi 2 MnO 3 ·(1 - y)LiTMO 2 (core surface layer), 0 < y < x < 1, and the TM element is Ni, Co, and Mn.

[0025] In the present invention, the phase structure gradient lithium-rich manganese-based material includes a monoclinic Li 2 MnO 3 phase and a rhombic LiTMO2 Phase; the monoclinic Li 2 MnO 3 The content of the phase preferably decreases from the inside to the outside, more preferably decreases linearly from the inside to the outside. 2 The content of the phase preferably increases sequentially from the inside to the outside, and more preferably increases linearly from the inside to the outside.

[0026] In a specific embodiment of the present invention, the chemical formula of the phase structure gradient lithium-rich manganese-based material can be specifically: core center 0.5Li 2 MnO 3 0.5Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2 , 0.3Li on the nuclear surface 2 MnO 3 0.7Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2 .

[0027] The gradient lithium-rich manganese-based material provided by the present invention includes a transition layer; the transition layer is a phase structure gradient lithium-rich manganese-based material doped with element A and element B, and the content of element A and element B preferably increases linearly from the inside to the outside independently. The transition layer of the present invention is doped with element A and element B, which can expand the lithium insertion and extraction diffusion channel of the gradient lithium-rich manganese-based material, improve the lattice constant, and the gradient lithium-rich manganese-based material after doping has a better layered structure, thereby further improving the comprehensive electrochemical performance of the gradient lithium-rich manganese-based material.

[0028] In the present invention, the thickness of the transition layer is preferably 2 to 10 nm, specifically 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.

[0029] In the present invention, the particle size of the phase structure gradient lithium-rich manganese-based material is preferably 1 to 30 μm, specifically 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm.

[0030] The gradient lithium-rich manganese-based material provided by the present invention comprises a perovskite layer; the chemical formula of the perovskite layer is A 1- w B w TMO 3, w can preferably be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, A is preferably a mixture of La and Sm, a mixture of Sm and Ba, a mixture of Ba and Sr, or a mixture of Sr and Pr, and B is preferably a mixture of Fe and Mo, a mixture of Mo and Cr, or a mixture of Fe and Cr.

[0031] In the present invention, TM elements are Ni, Co and Mn; the molar ratio of Ni to Co is preferably 0.05-0.3:0.05-0.2, specifically 0.05:0.05, 0.05:0.1, 0.05:0.15, 0.05:0.2, 0.1:0.05, 0.1:0.1, 0.1:0.15, 0.1:0.2, 0.2:0.05, 0.2:0.1, 0.2:0.15, 0.2:0.2, 0.3:0.05, 0.3:0.1 , 0.3:0.15 or 0.3:0.2; the molar ratio of Ni to Mn is preferably 0.05-0.3:0.5-0.9, specifically 0.05:0.5, 0.1:0.5, 0.15:0.5, 0.2:0.5, 0.3:0.5, 0.05:0.7, 0.1:0.7, 0.15:0.7, 0.2:0.7, 0.3:0.7, 0.05:0.9, 0.1:0.9, 0.15:0.9, 0.2:0.9 or 0.3:0.9.

[0032] In the present invention, the thickness of the perovskite layer is preferably 2 to 10 nm, specifically 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.

[0033] In a specific embodiment of the present invention, the chemical composition of the perovskite layer can be La 0.5 Fe 0.5 Ni 0.294 Co 0.112 Mn 0.594 O 3 、Sm 0.5 Mo 0.5 Ni 0.294 Co 0.112 Mn 0.594 O 3 ,La 0.3 Fe 0.7 Ni 0.294 Co 0.112 Mn 0.594 O 3 、PrNi 0.294 Co 0.112 Mn 0.594 O 3 、SmNi 0.294Co 0.112 Mn 0.594 O 3 、BaNi 0.294 Co 0.112 Mn 0.594 O 3 or SrNi 0.294 Co 0.112 Mn 0.594 O 3 .

[0034] The structure of the gradient lithium-rich manganese-based material provided by the present invention is as follows Figure 1 As shown, from the inside to the outside, it includes a phase structure gradient lithium-rich manganese-based material, a transition layer covering the surface of the phase structure gradient lithium-rich manganese-based material, and a perovskite layer covering the surface of the transition layer. The gradient lithium-rich manganese-based material provided by the present invention has a dense structure and is suitable for use as a positive electrode material for a battery.

[0035] The present invention also provides a method for preparing the gradient lithium-rich manganese-based material described in the above scheme, characterized in that it comprises the following steps:

[0036] The A source, the B source, water and the phase structure gradient lithium-rich manganese-based material are mixed and adsorbed and then annealed to obtain the gradient lithium-rich manganese-based material.

[0037] The present invention mixes source A, source B, water and a phase structure gradient lithium-rich manganese-based material (referred to as the first mixing to obtain a mixed solution) for adsorption. In the present invention, the source A preferably includes one or more of a chloride of element A, a sulfate of element A and a nitrate of element A, more preferably a mixture of a chloride of element A and a sulfate of element A, a mixture of a sulfate of element A and a nitrate of element A, or a mixture of a chloride of element A and a nitrate of element A.

[0038] In the present invention, the chloride of element A preferably includes one or more of lanthanum chloride, samarium chloride, barium chloride, strontium chloride and praseodymium chloride; the sulfate of element A preferably includes one or more of lanthanum sulfate, samarium sulfate, barium sulfate, strontium sulfate and praseodymium sulfate; the nitrate of element A preferably includes one or more of lanthanum nitrate, samarium nitrate, barium nitrate, strontium nitrate and praseodymium nitrate.

[0039] In the present invention, the B source preferably includes one or more of a chloride of element B, a sulfate of element B and a nitrate of element B, more preferably a mixture of a chloride of element B and a sulfate of element B, a mixture of a sulfate of element B and a nitrate of element B, or a mixture of a chloride of element B and a nitrate of element B.

[0040] In the present invention, the chloride of element B preferably includes one or more of ferric chloride, molybdenum chloride and chromium chloride; the sulfate of element B preferably includes one or more of ferric sulfate, molybdenum sulfate and chromium sulfate; the nitrate of element B preferably includes one or more of ferric nitrate, molybdenum nitrate and chromium nitrate.

[0041] The present invention utilizes a B source to provide transition metal ions, and through the ions doped in the phase structure gradient lithium-rich manganese-based material, a stronger MO chemical bond than active transition metals such as Ni, Co and Mn can be provided, and the structural stability of the material is improved by inhibiting the precipitation of lattice oxygen under high voltage; the cyclic stability and corrosion resistance of the material are further improved through the coating of transition metal ions, thereby improving the interface compatibility of the gradient lithium-rich manganese-based material.

[0042] In the present invention, the solid content of the phase structure gradient lithium-rich manganese-based material in the mixed solution is preferably 0.1 to 10 g / mL, specifically 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, 0.5 g / mL, 0.7 g / mL, 0.9 g / mL, 1 g / mL, 2 g / mL, 3 g / mL, 4 g / mL, 5 g / mL, 6 g / mL, 7 g / mL, 8 g / mL, 9 g / mL or 10 g / mL. The present invention adopts the above solid content to improve the coating effect, avoid uneven element distribution caused by too high solid content, and avoid too low solid content caused by less surface adsorbed elements and a large amount of waste liquid.

[0043] In the present invention, the first mixing is preferably: mixing source A and part of water to obtain source A solution, mixing source B and the remaining part of water to obtain source B solution, and mixing source A solution, source B solution and phase structure gradient lithium-rich manganese-based material.

[0044] In the present invention, the concentration of the A source solution is preferably 0.2-1 mol / L, specifically 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L.

[0045] In the present invention, the concentration of the B source solution is preferably 0.2-1 mol / L, specifically 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L. The present invention regulates the content of the A element and the B element in the gradient lithium-rich manganese-based material by using different concentrations.

[0046] In the present invention, the temperature of the first mixing is preferably 15-60°C, specifically 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C; the mixing time is preferably 2-48h, specifically 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h or 48h; the first mixing preferably includes ultrasonic dispersion.

[0047] In the present invention, after the first mixing, the process preferably further comprises washing and drying the obtained product in sequence.

[0048] In the present invention, the washing is preferably water washing; the water used for the water washing is preferably deionized water.

[0049] In the present invention, the drying temperature is preferably 50-120°C, specifically 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the heat preservation and drying time is preferably 10-20h, specifically 10h, 12h, 14h, 16h, 18h or 20h.

[0050] After the adsorption, the present invention anneals the obtained mixed solution to obtain the gradient lithium-rich manganese-based material. In the present invention, the annealing temperature is preferably 500-900°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, and the heat preservation annealing time is preferably 4-10h, specifically 4h, 5h, 6h, 7h, 8h, 9h or 10h; the annealing atmosphere is preferably one or more of air and oxygen. During annealing, the A source and B source substances decompose on the surface of the phase structure gradient lithium-rich manganese-based material and form perovskite. At the same time, part of the A element and the B element gradually diffuse into the interior of the phase structure gradient lithium-rich manganese-based material under the action of thermodynamics, thereby forming a gradient distribution.

[0051] The present invention uses a solution containing elements A and B to perform ion exchange on the surface of a phase structure gradient lithium-rich manganese-based material, and after annealing, forms a lithium-free perovskite layer and a transition layer gradiently doped with elements A and B on the surface of the phase structure gradient lithium-rich manganese-based material.

[0052] The present invention also provides the use of the gradient lithium-rich manganese-based material described in the above scheme or the gradient lithium-rich manganese-based material obtained by the preparation method described in the above scheme as a positive electrode material for a battery.

[0053] The gradient lithium-rich manganese-based material provided by the present invention has high discharge capacity, high average discharge voltage and high rate performance. The results of the embodiment show that the gradient lithium-rich manganese-based material provided by the present invention has a discharge specific capacity of 265 mAh g at 0.2C. -1 Above, the discharge capacity of 5C is 165mAhg -1 The average discharge voltage is above 3.65V, which can meet the requirements of batteries, especially lithium-ion batteries, for positive electrode materials and has broad application prospects.

[0054] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0055] Example 1

[0056] This embodiment prepares a gradient lithium-rich manganese-based material with a structure such as Figure 1 As shown, the surface of the phase structure gradient lithium-rich manganese-based material 1 is provided with a 4nm transition layer 2 and a 4nm perovskite layer 3; the chemical composition of the phase structure gradient lithium-rich manganese-based material is: the core center is 0.5Li 2 MnO 3 0.5Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2 , the nuclear surface is 0.3Li 2 MnO 3 0.7Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2 ; The transition layer 2 is a phase structure gradient lithium-rich manganese-based material doped with La and Fe elements, and the contents of the La and Fe elements increase independently from the inside to the outside; the chemical formula of the perovskite layer 3 is La 0.5 Fe 0.5 Ni 0.294 Co 0.112 Mn 0.594 O 3 (0.5 mol of La and 0.5 mol of Fe are dissolved on the surface of each mol of phase structure gradient lithium-rich manganese-based material).

[0057] The preparation method of the gradient lithium-rich manganese-based material in this embodiment includes the following steps:

[0058] The concentration of LaCl was 0.4 mol / L. 3 Aqueous solution, concentration of 0.4 mol / L FeCl 3The aqueous solution and 2 g of the phase structure gradient lithium-rich manganese-based material were ultrasonically dispersed at 25° C. for 24 h (the solid content of the solution obtained by ultrasonic dispersion was 0.4 g / mL), washed with deionized water, dried at 80° C. for 15 h, and annealed at 700° C. in an air atmosphere for 7 h to obtain the gradient lithium-rich manganese-based material.

[0059] The method for preparing the phase structure gradient lithium-rich manganese-based material comprises the following steps:

[0060] (1) Nickel sulfate (NiSO 4 6H 2 O), cobalt sulfate (NiSO 4 7H 2 O), manganese sulfate (MnSO 4 ·H 2 O) was dissolved in deionized water to prepare solution A and solution B with a total concentration of metal salts of 2 mol / L, wherein the molar ratio of Ni, Co and Mn in solution A was 0.21:0.08:0.71, and the molar ratio of Ni, Co and Mn in solution B was 0.343:0.1305:0.5265; 2 mol / L Na 2 CO 3 solution and 0.2 mol / L ammonia water;

[0061] (2) 600 mL of solution B prepared in step (1) was added to 600 mL of solution A in a stirring state through a constant flow pump. At the same time, a mixed salt solution obtained by mixing solution A and solution B was added to the reactor through a constant flow pump. Na 2 CO 3 The solution and ammonia water were added to the reactor in parallel through a constant flow pump, the stirring speed was controlled to be 1000 rpm, the pH value was 8.1, and the co-precipitation reaction was carried out at 55° C. for 10 h to obtain a phase structure gradient lithium-rich manganese-based material precursor;

[0062] (3) filtering, washing and drying the phase structure gradient lithium-rich manganese-based material precursor prepared in step (2), and mixing with Li 2 CO 3 The materials are uniformly mixed in a ratio of 1.6:1 between the molar number of Li and the total molar number of Ni, Co and Mn, pre-sintered at 500°C for 5 hours in an air atmosphere, and then heated to 900°C for 10 hours to obtain a phase structure gradient lithium-rich manganese-based material.

[0063] Example 2

[0064] In this embodiment, a gradient lithium-rich manganese-based material is prepared. The surface of the phase structure gradient lithium-rich manganese-based material is provided with a 2nm transition layer and a 2nm perovskite layer; the chemical formula of the phase structure gradient lithium-rich manganese-based material is: 0.5Li at the core center 2 MnO3 0.5Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2 , 0.3Li on the nuclear surface 2 MnO 3 0.7Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2 The transition layer is a phase structure gradient lithium-rich manganese-based material doped with Sm and Mo elements, and the contents of the Sm and Mo elements decrease independently from the outside to the inside; the chemical formula of the perovskite layer is Sm 0.5 Mo 0.5 Ni 0.294 Co 0.112 Mn 0.594 O 3 (0.5 mol of Sm and 0.5 mol of Mo are dissolved on the surface of each mol of phase structure gradient lithium-rich manganese-based material).

[0065] The preparation method of the gradient lithium-rich manganese-based material in this embodiment includes the following steps:

[0066] The concentration of Sm was 0.2 mol / L. 3 SO 4 , Mo with a concentration of 0.2 mol / L 3 SO 4 The phase structure gradient lithium-rich manganese-based positive electrode material is ultrasonically dispersed at 15° C. for 48 hours (the solid content of the ultrasonically dispersed solution is 10 g / mL), washed with deionized water, dried at 50° C. for 20 hours, and annealed at 500° C. for 10 hours in an air atmosphere to obtain the gradient lithium-rich manganese-based material.

[0067] Example 3

[0068] In this embodiment, a gradient lithium-rich manganese-based material is prepared. The surface of the phase structure gradient lithium-rich manganese-based material is provided with a 10nm transition layer and a 10nm perovskite layer; the chemical formula of the phase structure gradient lithium-rich manganese-based material is: 0.5Li at the core center 2 MnO 3 0.5Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2 , 0.3Li on the nuclear surface 2 MnO 3 0.7Li(Ni 0.42 Mn 0.42 Co 0.16 ) 2; The transition layer is a phase structure gradient lithium-rich manganese-based material doped with Sr elements, and the content of the Sr element decreases from the outside to the inside; the chemical formula of the perovskite layer is SrNi 0.294 Co 0.112 Mn 0.594 O 3 .

[0069] The preparation method of the gradient lithium-rich manganese-based material in this embodiment includes the following steps:

[0070] A source solution A with a concentration of 1 mol / L, a source solution B with a concentration of 1 mol / L and a phase structure gradient lithium-rich manganese-based material are ultrasonically dispersed at 60°C for 2 hours (the solid content of the ultrasonically dispersed solution is 0.5 g / mL), washed with deionized water, dried at 120°C for 10 hours, and annealed at 900°C in an air atmosphere for 4 hours to obtain the gradient lithium-rich manganese-based material.

[0071] Example 4

[0072] The preparation method of this embodiment is the same as that of embodiment 1, except that the annealing temperature is replaced with 300°C.

[0073] Example 5

[0074] The preparation method of this embodiment is the same as that of embodiment 1, except that the annealing temperature is replaced with 1000°C.

[0075] Comparative Example 1

[0076] The preparation method of this comparative example is the same as that of Example 1, except that LaCl is not used. 3 Solution.

[0077] Comparative Example 2

[0078] The preparation method of this comparative example is the same as that of Example 1, except that: this comparative example directly uses a phase structure gradient lithium-rich manganese-based material without surface modification.

[0079] Comparative Example 3

[0080] The preparation method of this comparative example is the same as that of Example 1, except that the phase structure gradient lithium-rich manganese-based material is replaced by a nickel-cobalt-manganese positive electrode material with a CAS number of 346417-97-8.

[0081] Test Example 1

[0082] The materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were respectively mixed with acetylene black and binder PVDF in a mass ratio of 8:1:1 to obtain a positive electrode slurry, which was evenly coated on an aluminum foil current collector, and then punched and rolled after drying to obtain a positive electrode sheet; a lithium sheet was used as the negative electrode sheet of the battery, and LiPF was used as the electrolyte. 6 / EC+DEC (Colod); Assemble the positive electrode, lithium sheet, separator and electrolyte into a 2032 button cell in a battery shell. After the battery is prepared, let it stand for 8 to 12 hours.

[0083] The batteries prepared from the materials of Examples 1 to 5 and Comparative Examples 1 to 3 were tested for discharge specific capacity and average discharge voltage at different rates (0.2C and 5C), and the test results are shown in Table 1. The average discharge voltage is calculated by measuring the voltage values ​​of the battery at different time points and averaging these voltage values ​​to obtain the average discharge voltage of the battery.

[0084] Table 1 Performance data of batteries prepared from materials of Examples 1 to 5 and Comparative Examples 1 to 3

[0085] Discharge capacity at 0.2C Average discharge voltage Discharge capacity at 5C Example 1 <![CDATA[282mAhg -1 ]]> 3.98V <![CDATA[193mAhg -1 ]]> Example 2 <![CDATA[279mAhg -1 ]]> 3.92V <![CDATA[194mAhg -1 ]]> Example 3 <![CDATA[280mAhg -1 ]]> 3.85V <![CDATA[192mAhg -1 ]]> Example 4 <![CDATA[267mAhg -1 ]]> 3.65V <![CDATA[170mAhg -1 ]]> Example 5 <![CDATA[266mAhg -1 ]]> 3.68V <![CDATA[168mAhg -1 ]]> Comparative Example 1 <![CDATA[263mAhg -1 ]]> 3.54V <![CDATA[164mAhg -1 ]]> Comparative Example 2 <![CDATA[271mAhg -1 ]]> 3.60V <![CDATA[180mAhg -1 ]]> Comparative Example 3 <![CDATA[265mAhg -1 ]]> 3.70V <![CDATA[160mAhg -1 ]]>

[0086] It can be seen from Table 1 that from the analysis of Examples 1 to 3, the present invention forms a transition layer and a perovskite layer on the surface of the lithium-rich manganese-based material on the basis of the phase structure gradient lithium-rich manganese-based material by ion exchange and then annealing. The perovskite layer acts as an oxygen buffer and can reversibly absorb oxygen ions, thereby hindering the release of oxygen. Through the provision of the transition layer and the perovskite layer, the anode stability window of the cathode is expanded, and the side reactions, impedance growth and electrochemical degradation on the surface are suppressed, thereby improving the discharge capacity, average discharge voltage and rate performance of the battery.

[0087] From the analysis of Examples 4 to 5, it can be seen that when the annealing temperature is too high or too low, if the annealing temperature is too high, the perovskite layer cannot be formed; if the annealing temperature is too low, the diffusion of the metal used for modification in the lattice of the lithium-rich manganese-based material cannot be activated, resulting in the inability to form a transition layer. In both cases, the performance of the material is reduced.

[0088] Analysis of Comparative Example 1 shows that without using LaCl 3 The solution, the formed perovskite layer and transition layer contain only transition metal elements, but no lanthanide metal elements, and its electrochemical performance decreases, indicating that the addition of lanthanide metals is very important for improving performance.

[0089] Analysis of Comparative Example 2 shows that the electrochemical performance of the battery decreases when the phase structure gradient lithium-rich manganese-based material is directly used without surface modification.

[0090] Analysis of Comparative Example 3 shows that after the phase structure gradient lithium-rich manganese-based material is replaced with the commercially available nickel-cobalt-manganese positive electrode material, the electrochemical performance of the battery decreases, indicating that the electrochemical performance will be improved only when the surface modification and phase structure gradient are combined.

[0091] It can be seen from the above embodiments that the gradient lithium-rich manganese-based material provided by the present invention has high discharge capacity, high average discharge voltage, high rate performance and excellent electrochemical performance.

[0092] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A gradient lithium-rich manganese-based material, characterized in that: It includes a phase structure gradient rich lithium manganese-based material, a transition layer covering the surface of the phase structure gradient rich lithium manganese-based material, and a perovskite layer covering the surface of the transition layer; The chemical formula of the phase structure gradient rich lithium manganese-based material is xLi2MnO3·(1-x)LiTMO2-yLi2MnO3·(1-y)LiTMO2, where 0 < y < x < 1, and the TM element is Ni, Co, and Mn; The chemical formula of the perovskite layer is A 1-w B w TMO3, 0≤w<1, A element is one or more of La, Sm, Ba, Sr and Pr, B element is one or more of Fe, Mo and Cr, TM element is Ni, Co and Mn; The transition layer is a phase structure gradient rich lithium manganese-based material doped with element A and element B, and the contents of element A and element B independently increase from the inside to the outside.

2. The gradient lithium-rich manganese-based material according to claim 1, characterized in that: The particle size of the phase structure gradient rich lithium manganese-based material is 1 to 30 μm.

3. The gradient lithium-rich manganese-based material according to claim 1 or 2, characterized in that: The thickness of the transition layer is 2 to 10 nm.

4. The gradient lithium-rich manganese-based material according to claim 1 or 2, characterized in that: The thickness of the perovskite layer is 2 to 10 nm.

5. The gradient lithium-rich manganese-based material according to claim 1 or 2, characterized in that: In the perovskite layer, the molar ratio of Ni and Co is 0.05 to 0.3:0.05 to 0.2, and the molar ratio of Ni and Mn is 0.05 to 0.3:0.5 to 0.

9.

6. The gradient lithium-rich manganese-based material according to claim 1, characterized in that: The chemical formula of the phase structure gradient lithium-rich manganese-based material is: core center 0.5Li2MnO3·0.5Li(Ni 0.42 Mn 0.42 Co 0.16 )O2, core surface 0.3Li2MnO3·0.7Li(Ni 0.42 Mn 0.42 Co 0.16 )O2.

7. The gradient lithium-rich manganese-based material according to claim 1, characterized in that: The chemical composition of the perovskite layer is La 0.5 Fe 0.5 Ni 0.294 Co 0.112 Mn 0.594 O3、Sm 0.5 Mo 0.5 Ni 0.294 Co 0.112 Mn 0.594 O3, La 0.3 Fe 0.7 Ni 0.294 Co 0.112 Mn 0.59 4O3、PrNi 0.294 Co 0.112 Mn 0.594 O3、SmNi 0.294 Co 0.112 Mn 0.594 O3、BaNi 0.294 Co 0.112 Mn 0.594 O3 or SrNi 0.294 Co 0.112 Mn 0.594 O3.

8. The method for preparing the gradient lithium-rich manganese-based material according to any one of claims 1 to 7, characterized in that: It includes the following steps: Mix an A source, a B source, water, and a phase structure gradient rich lithium manganese-based material, perform adsorption and then annealing to obtain the gradient rich lithium manganese-based material.

9. The preparation method according to claim 8, characterized in that: The temperature of the annealing is 500 to 900 °C, and the holding annealing time is 4 to 10 h; The atmosphere of the annealing is one or several of air and oxygen.

10. Application of the gradient rich lithium manganese-based material according to any one of claims 1 to 7 or the gradient rich lithium manganese-based material obtained by the preparation method according to any one of claims 8 to 9 as a cathode material of a battery.

Citation Information

Patent Citations

  • Phase structure proportionally and gradiently changed lithium-enriched layered oxide material and preparation method thereof

    CN107785551A

  • Perovskite type oxygen vacancy compound modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN112909256A

  • Water-based slurry production with cathode active material coated with a solid electrolyte, production of an electrode from it and production of a lithium-ion battery cell

    DE102018219589A1

  • Improved lithium metal oxide cathode materials and method to make them

    WO2015094847A1

  • Positive electrode material, and preparation method therefor and use thereof

    WO2024164440A1